(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the work, a theoretical study of the mechanical characteristics of the composite of the Al-Al2O3 system. The substantiation of the lowered values of the strength of the composite specimens is proposed, :interphase zone (for which the composition and approximate thickness is determined) on the mechanical properties of the material has been carried out; it is shown that, within the framework of the classical model of multilayer cylindrical fibers, the resulting interfacial zones do not significantly affect the properties of the material, but the level of residual stresses can be affected.